2007
DOI: 10.3354/meps334245
|View full text |Cite
|
Sign up to set email alerts
|

High genetic connectivity across the Indian and Pacific Oceans in the reef fish Myripristis berndti (Holocentridae)

Abstract: To assess patterns of connectivity among populations of an Indo-Pacific reef fish, we surveyed mtDNA of the bigscale soldierfish Myripristis berndti (Holocentridae), which is concentrated on reefs at intermediate depths, but occurs to at least 160 m. Our multi-scale approach included sampling at 11 sites spanning the entire range of the species from the western Indian Ocean to the eastern Pacific, across 240°of longitude (total N = 278), and 9 islands throughout one of the largest and most isolated archipelago… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
140
2
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 142 publications
(153 citation statements)
references
References 47 publications
10
140
2
1
Order By: Relevance
“…This condition might be due to no genetic exchange between those two islands because seeds transportation mainly tends to occur on the island. This result was also similar to another part of Craig et al (2007) and Craig et al (2009) studies in two reef fish species where significant genetic differences were found among large geographically separated populations. Moreover, strong genetic structures were also observed among geographically separated cyprinids populations (Durand et al, 2002) and among Orizyas latipes populations Takehana et al (2003).…”
Section: Resultssupporting
confidence: 77%
See 3 more Smart Citations
“…This condition might be due to no genetic exchange between those two islands because seeds transportation mainly tends to occur on the island. This result was also similar to another part of Craig et al (2007) and Craig et al (2009) studies in two reef fish species where significant genetic differences were found among large geographically separated populations. Moreover, strong genetic structures were also observed among geographically separated cyprinids populations (Durand et al, 2002) and among Orizyas latipes populations Takehana et al (2003).…”
Section: Resultssupporting
confidence: 77%
“…In case of Sumatera strains, our study has a similar result to a part of Craig et al (2007) study in reef fish Myripristis berndti where no genetic differences were observed in rather narrow areas such as within Central Pacific (Φ st = -0.007, p = 0.634), within Indian Ocean (Φ st = -0.027, p = 0.528), and within the east Pacific (Φ st = -0.061, p = 0.920). The present study and previous study from Craig et al (2007) indicates low rates of molecular evolution in mitochondrial cytochrome b gene which lead to no genetic structuring among populations in small geographic scales. Therefore, it is not surprising if a low level of genetic differences were observed in cyt b gene among morphologically different giant gourami strains in Sumatera.…”
Section: Resultssupporting
confidence: 72%
See 2 more Smart Citations
“…Nonetheless, fishes with a long pelagic larval stage tend to have extensive dispersal, broad ranges and dominate communities on isolated islands (Horne et al, 2008;Reece et al, 2011;. Some of the most dispersive reef fishes are those that can stay in the water column after transforming from larva to juvenile (or pre-juvenile), including trumpetfishes (Bowen et al, 2001), squirrelfishes (Craig et al, 2007) and (most relevant) other surgeonfishes (Thresher, 1984). The sister species surveyed here provide additional examples of highly dispersive fishes, a trait that may be a general feature of the genus Acanthurus (Eble et al, 2011).…”
Section: Is There Gene Flow From the Suture Zone Via Hybrid Offspring?mentioning
confidence: 99%